KARAKTERISTIK HEDONIK DAN GIZI CENDOL IKAN NILA (OREOCHROMIS NILOTICUS) DENGAN PENAMBAHAN KOPI - Anggraeni, Novia; Rizkaprilisa, Windy; Widhi Hapsari, Martina; Paramastuti, Ratih (Jurnal Borneo Saintek, 2023)
Cendol is one of the popular drinks in Indonesia which is made from flour with incomplete nutritional content, so it is necessary to modify the formulation of cendol by adding tilapia fish meat and coffee grounds to complement the nutritional value of cendol products. The purpose of this study was to determine the effect of the addition of coffee grounds on consumer acceptance and the nutritional value of tilapia cendol products. This study used a completely randomized design (CRD), with 4 treatments adding coffee powder 0 g, 4 g, 6 g, and 8 g. The results showed that the addition of coffee grounds had an effect on the hedonic results of tilapia cendol. The best cendol according to consumer acceptance based on hedonic code K2 results with the addition of 6 g coffee powder with a moisture content of 65.34%, ash content of 0.48%, fat content of 0.52%, protein content of 11.13%, and carbohydrate content of 23 .53%.